A critical analysis of the military strategic lessons learned from South Africa’s participation in the force intervention brigade in the Democratic Republic of the Congo - Pieterse, Johan Christiaan (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMil)--Stellenbosch University, 2022.